A 3D morphometric follow-up analysis after frontoorbital advancement in non-syndromic craniosynostosis. Issue 8 (October 2015) - Martini, M.; Schulz, M.; Röhrig, A.; Nadal, J.; Messing-Jünger, M.
Abstract: Objective: Frontoorbital advancement (FOA) in patients with non-syndromic craniosynostosis mainly addresses the aesthetic and functional correction of the frontoorbital region. To help define the operative strategy and any follow-up assessments after surgical correction, objective parameters describing the critical regions of skull deformity are essential. Based on 3D morphometric analysis, new parameters for the documentation of changes of the frontoorbital bandeau were developed in a prospective study. Methods and materials: In a prospective series, 13 children with non-syndromic craniosynostosis (seven metopic, four unilateral coronal, and two bilateral coronal) treated with frontoorbital advancement, underwent detailed morphometric and volumetric evaluation using a 3D light optical scan system (3D-Shape, Erlangen, Germany). Measurements were obtained preoperatively and at 3, 6 and 12 months postoperatively with newly developed parameters generated by cephalometric analysis software (Onyx Ceph, Image Instruments, Chemnitz, Germany). Results: In most patients, frontoorbital advancement resulted in stable long-term results without growth inhibition and with normalization or improvement of ongoing skull development. The mean frontal angle was 145° and the frontoparietal angle 137–140°. The cephalic index was normalized or markedly improved. Head circumference and head height increased significantly ( p  = 0.001 and p  = 0.002, respectively). These changes were confirmed in all postoperative measurements. Conclusion: During the 12-month follow-up period all angle parameters proved to be stable and no major impairment of normal skull growth was observed after FOA. The frontoorbital angle is a useful parameter in evaluating long-term outcome. The frontoparietal angle is important for the stability of the frontoparietal region, in which a certain growth inhibition may be observed postoperatively.